Development of method foundations for generating noise-like signals based on direct sequence spread spectrum of timing signal structures - Korchynskyi, Volodymyr; Kildishev, Vitalii; Bektursunov, Daniyar; Havel, Serhii; Stepanov, Vadym; Slavych, Vasyl; Petrovskyi, Ruslan (Technology audit and production reserves, 2026)
The object of the research is the process of forming complex noise-like signals based on timer signal constructions in secure communication systems operating under conditions of electronic warfare and counteraction to electronic intelligence systems. The problem addressed in the paper is the lack of a theoretical framework for spectrum spreading of non-positional signals. An example of such signals is timer signal constructions, which are characterized by a more complex and variable temporal pulse structure within a combination. The research solves the problem of developing a direct-sequence spread spectrum method for non-positional signals with a variable temporal pulse structure. It is shown that the classical spread spectrum method, designed for positional signals with fixed bit interval duration, cannot be directly applied to timer signal constructions. The proposed method provides for spectrum spreading not of an individual time interval of a binary bit element, but of the entire timer signal combination. A necessary condition for spectrum spreading in this case is the optimal selection of timer signal design parameters. This ensures the required interference immunity of the signal constructions, taking into account the interference level in the channel and the assessment of structural concealment. The obtained results made it possible to establish the relationship between interference immunity and the level of concealment of timer signal constructions. It is shown that varying the parameters of timer noise-like signal formation significantly complicates their detection, recognition, and analysis by electronic intelligence means. According to the results of correlation analysis, the correlation coefficient varies in the range from 0.125 to 0.516, indicating reduced predictability and an increased level of structural concealment of the generated signal constructions. The effectiveness of the proposed solution is explained by the fact that reception of broadband constructions is possible only when the correlation receiver is configured according to the timer signal design parameters. This practically prevents the reception of broadband timer signals generated with different design parameters, as well as by means of conventional classical correlation receivers. The practical application of the results is possible in the design of secure special-purpose communication systems operating under conditions of intensive electronic countermeasures.